A DFT study on the metal ion selectivity of deferiprone complexes. (June 2020) - Kaviani, Sadegh; Izadyar, Mohammad; Housaindokht, Mohammad Reza
Graphical abstract: Deferiprone is a good candidate for selective complex formation with Al 3+ in the presence of different metal ions. Highlights: DFT study was performed on the metal ion selectivity of deferiprone complexes. Charge transfer occurs from the oxygen atoms of deferiprone to the metal ions. QTAIM analysis confirm that the strongest M - O bond is found in [Al(DFP)3 ]. Deferiprone is a good candidate for selective complex formation with Al 3+ . Abstract: In this work, systematic density functional theory (DFT) calculations were performed to study the interactions of various metal ions (Al 3+, Fe 3+, Co 2+, Ni 2+, Cu 2+, and Zn 2+ ) and the clinically useful chelating agent called deferiprone (DFP) at the M05-2X/6-31G(d) level of theory. The thermodynamic parameters of metal-deferiprone complexes were determined in water. Based on the obtained data, the theoretical binding energy trend is as follows: Al 3+ > Fe 3+ > Cu 2+ > Ni 2+ > Co 2+ > Zn 2+, confirming that [Al(DFP)3 ] has the most interaction energy. Moreover, Natural bond orbital analysis was employed to determine and analyze the natural charges on different atoms and charge transfer between the metal ions and ligands (oxygen atoms) as well as the interaction energy (E(2)) values. The calculated value of ƩE(2) (donor-acceptor interaction energy) for [Al(DFP)3 ] complex is higher than other complexes, which is according to energy analysis. To confirm the type of effective interactions and bonding properties in the water, the quantum theory of atoms in molecules (QTAIM) analysis was applied. QTAIM analysis confirmed that the strongest M - O bond is found in the [Al(DFP)3 ] complex. The calculated topological properties at the bond critical points, such as the ratio of the kinetic energy density to the potential energy density, -G(r)/V(r), electronic energy density, H(r), confirm that M - O bonds in the Al-deferiprone complex are non-covalent, while in other complexes, they are electrostatic and partially covalent.